Geology of Dhangarhi-Dandeldhura road section and its regional significance - Bashyal, R. P. (Journal of Nepal Geological Society, 1981)
The present paper deals with the geological section of the Dhangarhi Dandeldhura Road in the far Western Nepal. The section, south to north, crosses the Gangetic plain, Siwaliks, and the Lesser Himalayan metasedimentary and crystalline rocks. Two tectonic units to the north of MBT, Budar Metasedimentary Complex and Dandeldhura Crystalline Complex, are recognized. The latter which is equivalent to the Almora Crystalline Nappe, is thrust over the Lesser Himalayan metasedimentary complex along the Goganpani Thrust and has been preserved in the synclinal structure. The Budar Complex comprising Budar quartzites and Rupaskanra Phyllites, is correlable to Nagthat quartzites (Krol Nappe?) and Ramgarh unit (Valdiya, 1980) or the Chail Nappe (Fuchs & Sinha, 1978) of the Kumaun Himalayas.